MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL GUIDED NOTE TAKING PADA SISWA KELAS IV SD INPRES JONGAYA - Nurhalimah Tulsa’dia; Ernawati; Andi Ardhilah Wahyudi (STKIP Subang, 2025)
The problem in this study is that students are less interested and attracted to mathematics learning, with that mathematics learning becomes low so that there are students who do not complete and do not reach the KKM score. This study to improve mathematics learning outcomes through the Guided Note Taking model in fourth grade students of SD Inpres Jongaya. Through implementing this Guided Note Taking model. This type for research is Class Action Research whish cinsists of two cycles, namely cysles I and cycles II, each cycle being carried out in 4 meetings. The result showed that in cycle I there were 28 students with an average score of 69,79% with a complete score of 35%. So from cycle I, students did not meet the minimum completeness criteria fourthemore, in cycle II, 28 students experienced an increase, namely with an average score of 89,82% with a complete score of 100%. So there is an increase in mathematics learning outcomes for class IV students from cycle I to cycle II. This shows that applying the Guided Note Taking learning model can improve students’ mathematics learning otcomes